Undergraduate Student Award in Environmental Chemistry, Division of Environmental Chemistry - Antoniou, Maria G. (My University, 2026)
My undergraduate advisee in research Danae Pantelide: Undergraduate Student Award in Environmental Chemistry, Division of Environmental Chemistry, American Chemical Society, April 2017.
Keywords: Sciences